Development and Effects of Supplementary Material about Electronic Fetal Monitoring for Nursing Students - Gye Jeong Yeom; Il OK Kim (Korean Society of Women Health Nursing, 2016)
PURPOSE: This study aimed to develop supplementary material about the electronic fetal monitoring for nursing students, and to test the effects on electronic fetal monitoring related knowledge and confidence on nursing performance in delivery room. METHODS: Totally 58 nursing students were recruited either experimental group (n=30) or a control group (n=28). A non-equivalent control group pretest-posttest design was employed to test the effects on fetal monitoring related knowledge and confidence on nursing performance in delivery room. The supplementary material about the electronic fetal monitoring was developed based on Analysis, Design, Development, Implement and Evaluation (ADDIE) model. Fetal monitoring related knowledge and confidence on nursing performance in delivery room were self-reported by the scales that author developed. Data were collected at pre-test and after the 6-week intervention. RESULTS: There was significant difference in confidence on nursing performance in delivery room between two groups after intervention. CONCLUSION: These findings suggest the importance of the supplementary material about the electronic fetal monitoring for nursing students to improve confidence on nursing performance in delivery room.